Empowering SMPIT Al-Fikri Makassar Students through Training in Making Natural Body Care Products - Nurmaya Effendi; Dewi Yuliana; Audia Triani Olii; Andi Trihadi Kusuma; Aminah; Asni Amin; Hadawiah (Altifani Journal: International Journal of Community Engagement, 2026)
Adolescents are in a development stage characterized by identity exploration and are often easily influenced by lifestyle trends, including cosmetic use. However, many teenagers still have limited awareness regarding the safety of ingredients used in commercial cosmetic products, which may potentially cause adverse effects on skin health. On the other hand, natural-based body care products are increasingly preferred due to their perceived safety and environmental friendliness. This community engagement program aimed to improve the knowledge and practical skills of SMPIT Al-Fikri Makassar students in selecting safe cosmetics and producing natural body care products, namely deodorant spray, deodorant stick, and lip balm. A total of 138 students participated in the program, while evaluation was conducted on 30 representative respondents selected purposively from each class. The program applied the Asset-Based Community Development (ABCD) approach by optimizing locally available natural resources. The implementation stages included socialization, education on safe, natural, and healthy cosmetics, product-making workshops, and evaluation using pre-test and post-tests methods. The results showed that the participants’ knowledge increased from 45-53% (pre-test) to 85-90% (post-test). Practical skills in product preparation also improved from 40-45% (pre-test) to 87-90% (post-test). These findings indicate that practice-based training is effective in enhancing cosmetic literacy and empowering adolescents to produce safe and eco-friendly natural body care products. Then, we hope that SMPIT Al-Fikri Makassar students will be able to apply the knowledge and skills gained to make informed choices and adopt healthy practices in their daily lives.